„JUŻ NOC ZAPROWADZIŁA CIEMNE RZĄDY SWOJE” - Rozmysł, Michał (Colloquia Litteraria, 2019)
„Już Noc zaprowadziła ciemne rządy swoje” [review of Dominika Skiba, Anna Rej, Marian Ursel (eds.), Noce romantyków. Literatura kultura, obyczaj, Cracow: Universitas, 2015] The reviewed work gathers the proceedings of a conference held at the University of Wrocław between 17-18 October 2013. The thirty- -one contributions are divided into four thematic areas. The volume includes pieces by established and renowned scholars as well as be- ginner students of Romanticism. The studies focus on Polish and French Romanticisms. They touch upon the relationship between arts in the nineteenth century and the extending of the Romantic tradition into later epochs.